2016
DOI: 10.1016/j.ijheh.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Levels of persistent contaminants in relation to fish consumption among older male anglers in Wisconsin

Abstract: Fish are an important source of nutrients which may reduce risk of adverse health outcomes such as cardiovascular disease; however, fish may also contain significant amounts of environmental pollutants such as mercury, polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and perfluorinated compounds (PFCs, also called perfluoroalkyl compounds), which confer increased risk for adverse health effects. The Wisconsin Departments of Health Services and Natural Resources developed a survey instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
0
17
1
1
Order By: Relevance
“…Exposure biomarkers (e.g., blood, hair, or urine Hg concentrations) are important tools for monitoring and estimating Hg exposure in human populations. However, discrepancies exist in the relationships between actual exposure as measured through dietary intake or inhalation estimates and realized exposure as measured through biomarkers (Christensen et al 2016 ; Awata et al 2017 ; Branco et al 2017 ), suggesting that there are other drivers that modify the pathway from actual to realized Hg exposure. Over the past decade research has shown that genetic and epigenetic factors may influence realized Hg exposure (reviewed by Basu et al 2014 ; Llop et al 2015 ).…”
Section: Domain 2: Global Extrinsic and Individual/molecular-level Inmentioning
confidence: 99%
“…Exposure biomarkers (e.g., blood, hair, or urine Hg concentrations) are important tools for monitoring and estimating Hg exposure in human populations. However, discrepancies exist in the relationships between actual exposure as measured through dietary intake or inhalation estimates and realized exposure as measured through biomarkers (Christensen et al 2016 ; Awata et al 2017 ; Branco et al 2017 ), suggesting that there are other drivers that modify the pathway from actual to realized Hg exposure. Over the past decade research has shown that genetic and epigenetic factors may influence realized Hg exposure (reviewed by Basu et al 2014 ; Llop et al 2015 ).…”
Section: Domain 2: Global Extrinsic and Individual/molecular-level Inmentioning
confidence: 99%
“…In 2012–2013, the Wisconsin Departments of Health Services conducted a biomonitoring study of male anglers aged 50 years and older. Participants (n = 154) had somewhat higher blood mercury levels compared with the U.S. general population, and the consumption of fish from the Great Lakes area was associated with higher levels of blood mercury, PCBs and PFAS (Christensen et al, 2016a, 2016b).…”
Section: Discussionmentioning
confidence: 97%
“…Vulnerable populations include women of childbearing age, pregnant women, fetuses, nursing infants, children, the elderly, certain ethnic groups, and anglers (Johnson et al, 1998). Urban communities living in or near contaminated watersheds and indigenous communities that live off the land in the Great Lakes basin are at risk of high exposure through eating locally caught fish, aquatic plants, and wildlife (Fitzgerald et al, 2004; Schaeffer et al, 2006; Turyk et al, 2006; Knobeloch et al, 2009; Christensen et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Although the production of PCBs has been banned globally for decades, PCB concentrations remain relatively high in the environment, especially in urban areas, and unintentional production still occurs in the cement and steel industry (Song et al, ). Due to their persistence and wide spread in the environment, mercury, PCBs, and PFASs often accumulate in organisms such as fish and farm animals (Christensen et al, ; Weber et al, ). Well‐known cohort studies in the Faroe Islands have associated autoantibodies with prenatal and childhood exposure to environmental chemicals such as methylmercury, PCBs, and PFASs in Faroese children (Osuna, Grandjean, Weihe, & El‐Fawal, ).…”
Section: Autoimmunitymentioning
confidence: 99%